PENGARUH LEVERAGE TERHADAP ISLAMIC SOCIAL REPORTING DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI PADA BANK UMUM SYARIAH - Heru Ginanjar; Heri Junaidi; Titin Hartini (Jurnal Darma Agung, 2022)
Islamic Social Reporting is a social performance reporting system for companies that carry out business activities with sharia principles. In particular, this index is an extension of a standard or social performance reporting system that includes people's expectations not only about the role of companies in the economy, but also the role of companies from a spiritual perspective. This study aims to analyze the effect of the independent variable, namely Leverage on Islamic Social Reporting with Firm Size as a moderating variable in Islamic Commercial Banks. This study uses secondary data from the 2015-2019 Sharia Banking Annual Reports and Good Corporate Governance Reports registered with Bank Indonesia. This research uses Structural Equation Modeling (SEM) software, especially Partial Least Square (PLS). The results of this study are that leverage has no effect on Islamic Social Reporting and Firm Size moderates the effect of leverage on Islamic Social Reporting.